Contrasting Similar Words Facilitates Second Language Vocabulary Learning in Children by Sharpening Lexical Representations - Baxter, Peta; Droop, Mienke; van den Hurk, Marianne; Bekkering, Harold; Dijkstra, Ton; Leoné, Frank (Frontiers in Psychology, 2021)
This study considers one of the cognitive mechanisms underlying the development of second language (L2) vocabulary in children: The differentiation and sharpening of lexical representations. We propose that sharpening is triggered by an implicit comparison of similar representations, a process we call contrasting. We investigate whether integrating contrasting in a learning method in which children contrast orthographically and semantically similar L2 words facilitates learning of those words by sharpening their new lexical representations. In our study, 48 Dutch-speaking children learned unfamiliar orthographically and semantically similar English words in a multiple-choice learning task. One half of the group learned the similar words by contrasting them, while the other half did not contrast them. Their word knowledge was measured immediately after learning as well as 1 week later. Contrasting was found to facilitate learning by leading to more precise lexical representations. However, only highly skilled readers benefitted from contrasting. Our findings offer novel insights into the development of L2 lexical representations from fuzzy to more precise, and have potential implications for education.